Membaca Pemikiran Taha Abdurrahman Tentang Etika Politik Islam - Muhammad Rizky HK (UIN Mataram, 2020)
This article will discuss the possibility to reconstruct the Islamic political ethics based on Taha Abdurrahman’s thought about ethics. As a field of study Islamic political ethics provide us the way out from normative perspective which seen the relation between Islam and state are just talking about khilafah as a system, and form of state to the ethic-substantive perspective which emphasize the implementation of the values of Islamic teachings in every political action. Taha Abdurrahman, which has been widely known as an Islamic Philosophers, and one of a biggest theoriest in ethic. The Authors tried to explore Taha’s thought on ethics to rebuild the Islamic political ethics.